Microbial ecology and C and N dynamics in Agroecosystems - Fabrizzi, Karina Paola (Kansas State University, 2006)
Soil C sequestration in agricultural ecosystems is an immediate and significant option to mitigate the increase in the atmospheric CO2 concentration. The objectives of this study were to determine 1) the influence of crop and soil management practices applicable to Kansas (i.e., tillage, N fertilization, and crop rotations) on soil C and N, C sequestration rates, soil aggregation and aggregate-associated C and N; and 2) the influence of long-term tillage practices on SOC and total N, soil aggregation and aggregate-associated C and N in three soil types: an Oxisol (Brazil), a Vertisol (Argentina), and a Mollisol (Kansas, USA). The Kansas experiments included: tillage (conventional tillage (CT), reduced tillage (RT) and no-tillage (NT)) and native prairie; nitrogen (N) fertilization rates; and crop rotations comprising various combinations of winter wheat (Triticum aestivum L.), grain sorghum (Sorghum bicolor L. Moench), and soybean (Glycine max L. Merrill). The presence of a fallow period negatively affected C sequestration rates even under NT systems. Nitrogen fertilization generally increased C sequestration rates. Rotations that contained wheat or sorghum had the greatest C sequestration rates while continuous soybean had the lowest rates. Cultivation decreased the amount of macroaggregates with a concomitment increased in the amount of microaggregates. Wheat and sorghum increased total C in the macroaggregate fraction (>250 mm) under NT while soybean had the lowest C concentration. Cultivation reduced microbial biomass C and N and potentially mineralizable C and N. The combination of conservation tillage and rotations that produced a greater amount of residue had greater C sequestration rates. In the Oxisol, NT had greater amounts of large macroaggregates (>2000 mm) than CT, however no differences between tillage practices were detected in the Vertisol and Mollisol. Cultivation of native grassland reduced the amount of macroaggregates and the associated C and N concentration; however NT tended to be more similar to the native grassland. Overall, our results indicated that the use of conservation tillage could be an important strategy to sequester C in these agroecosystems. The adoption of management practices that enhance C sequestration would be important for reducing GHGs emissions and maintaining the sustainability of agricultural systems.
Keywords: carbon sequestration; management practices; microbial communities; soil aggregation; Carbon and Nitrogen pools; Agriculture, Agronomy (0285)